Impact of a Multidisciplinary eBoard on the Management of Patients With Complex Inflammatory Bowel Disease. Issue 2 (20th August 2019) - Quinn, Kevin P; Prothero, Breanne L; Russell, Jennifer M; Hegge, Ryan J; von Bormann, Alexander G; Larson, Putchalee A; Christofferson, Sara N; Smyrk, Thomas C; Mathis, Kellie L; Goenka, Ajit H; Sheedy, Shannon P; Bruining, David H; et al.
Abstract: Background: We aim to assess the impact of a multidisciplinary inflammatory bowel disease (IBD) conference on the management of patients with complex IBD. Methods: Data were collected during each conference from February 2017 through October 2018 with chart review performed at 6 months to determine if conference recommendations were successfully implemented. Results: Eighty-five patients were discussed. The presenting diagnosis was changed by 11.8%. Recommendations for further testing, medical therapy, and surgery were successfully implemented in 77.1%, 98.1%, and 88.4%, respectively. Conclusions: This study supports the role of IBD multidisciplinary conferences in the management of patients with complex IBD. Lay Summary: Quinn et al. provide a roadmap for creating a virtual teleconference that includes multiple specialties that may serve as a resource for providers outside of referral centers and shows the ability to use the recommendations to improve patient care.